PERENCANAAN MANAJEMEN ASET IRIGASI (PMA): PENGEMBANGAN KONSEPSI DAN IMPLEMENTASINYA DI INDONESIA - Sigit Supadmo Arif; Abi Prabowo; Anjar Suprapto; Judy Kurniawan (Jurnal Keteknikan Pertanian, 2007)
ABSTRACT The Government of Republic Indonesia had positively responded the emerging of new paradigm on irrigation management. Government Act No. 7/2004 on water resources as well as tile new Government Regulation No. 20/2006 on irrigation state about concept on good governance in management of water resources as well as irrigation management. One of implementation of the concept is application of irrigation management asset. The Department of Agricultural Engineering, Gadjah Mada University. Yogyakarta had been developed the concept of irrigation asset management plan since 1995. This paper aims to discuss the concept development and its implementation in several irrigation systems in Java. Even though some constraints were also found, in some extend the implementation of irrigation asset management plan could help the management of irrigation system in providing several information in transparent way to all stakeholder especially farmers. Diterima: 15 Pebruari 2007; Disetujui: 4 Maret 2007